Quality indicators in telephone nursing - An integrative review - Silje Rysst Gustafsson; Irene Eriksson (Wiley, 2021)
Abstract Aim The aim of this study was to identify factors that indicate quality in telephone nursing. Design An integrative literature review. Method A literature search was performed in October 2018, in the PubMed, CINAHL, Cochrane Library, Academic Search, PsycINFO, Scopus and Web of Science databases. A total of 30 included were included and data that corresponded to the study's aim were extracted and categorized along the three areas of quality as described by Donabedian (Milbank Quarterly, 83, 691), namely structure, process and outcome. Results The analysis revealed ten factors indicating quality in telephone nursing (TN): availability and simplicity of the service, sustainable working conditions, specialist education and TN experience, healthcare resources and organization, good communication, person‐centredness, competence, correct and safe care, efficiency and satisfaction. TN services need to target all ten factors to ensure that the care given is of high quality and able to meet today's requirements for the service.